Pengaruh Model Discovery Learning Berbantuan LKPD Berbasis HOTS Terhadap Kemampuan Berpikir Kritis Peserta Didik - Sulisningtyas, Sabrina; Fauziah, Anna; Refianti, Rani (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
The purpose of this study was to determine the effect of Discovery Learning model assisted by HOTS-based LKPD on students' critical thinking skills. The type of research used is Quasi Experiment Design. The research was conducted at SMP Negeri 7 Lubuklinggau with the research population was class VIII. The research sample was class VIII.5 as the experimental class and class VIII.6 as the control class. The sampling technique used Probability Sampling with Cluester Random Sample. Data analysis includes normality test, homogeneity test and hypothesis testing. In this study, Chi Kuadrat was used to test the normality of data, F (Fisher) test for data homogeneity test, and pseudo t-test for hypothesis testing. The results of testing the hypothesis of the final ability of students show that  , namely 3.977>1.701 then Ho is rejected which means that the average score of critical thinking skills of experimental class students is greater than the control class (. So it can be concluded that there is an effect of the Discovery Learning model assisted by HOTS-based LKPD on students' critical thinking skills.